Keragaman Genetik, Morfologi dan Produksi Tanaman Sagu Dataran Tinggi Latimojong Kabupaten Luwu: Keragaman Genetik, Morfologi dan Produksi Tanaman Sagu Dataran Tinggi Latimojong Kabupaten Luwu - Masluki; Mutmainnah (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Luwu Regency is one of the centers of sago distribution in South Sulawesi Province, both in the lowlands and highlands. The existence of genotypes and phenotypes in different locations can provide information related to the level of sago plant diversity. Information on the diversity of sago accessions from the community is generally only based on morphological and production characters so that it is unstable due to environmental influences.This research aims to obtain data and information on genetic diversity based on RAPD molecular markers, morphological characteristics and production potential of various sago accessions in the highlands. The research method was carried out through the stages of observing morphological and production characters by direct observation in the field. Genetic diversity analysis was carried out using the RAPD molecular marker test using 9 selected primers. The samples used were young sago leaves. Sago samples for the purposes of observing morphology and production in felled ripe sago stands were carried out using destructive sampling by cutting down sample sago trees. The selected sago has entered the mature felling phase in each accession which has the same morphological characteristics based on visual characteristics and information from key respondents. The average polymorphic band was 7.33 while the average monomorphic band was 3.22. The highest percentage of polymorphism was 88.88% while the lowest was 41.67 %. Some accessions have the highest dissimilarity coefficient of 70%, while the lowest similarity coefficient value is 18 %. Latimojong highland sago has a low production average of 118.24 kg tree-1